Oriented immobilization of enzyme–DNA conjugates on magnetic Janus particles for constructing a multicompartment multienzyme system with high activity and stability. Issue 36 (19th August 2020) - Shen, Hao; Zheng, Xuelian; Zhou, Zixin; He, Wenting; Li, Mengqi; Su, Ping; Song, Jiayi; Yang, Yi
Abstract : An exquisitely designed multicompartment multienzyme system has been constructed by encapsulating poly-tannic acid (pTA) on the surface of enzyme–DNA conjugates, which are anchored on magnetic Janus particles. Abstract : Various organelles ( e.g., mitochondria and chloroplasts) have a multicompartment structure, providing superior function of material transformation, selective segregation and energy conversion. Enlightened by the elegant evolution of nature, intended isolation of the biochemical process by cooperative multicompartments in cells has become an appealing blueprint to construct bioreactors. In this study, we develop a "soft separation" way to establish a delicate multicompartment multienzyme system (MMS) with polyphenol-encapsulated enzyme–DNA conjugates, which are anchored on magnetic Janus particles, providing a biomimetic catalysis network with the model cascade reactions in confinement. The well-designed MMS exhibits preferable bioactivity benefitting from the dependable DNA bridges and the oriented immobilization of enzymes, while the polyphenol shell further protects the anchored enzymes from exterior attacks, such as heat and enzymatic degradation. Moreover, by applying the MMS as nanomotors, the asymmetrical distribution of enzymes on Janus particles is found to improve mutual elevation between the self-driven locomotion and enzyme-mediated reactions, delivering enhanced dispersal ability and bioactivity. Owing to the excellent enzymatic activity, promoted stability and satisfying biocompatibility, the assembled MMS is proved to be promising for the in vitro and intracellular sensing of glucose, showing significant potential for biochemical analysis applications.